Stainless steel blasting abrasives
The use of austenitic chromium manganese steel in stainless steel blast abrasives addresses the limitations of current materials by enhancing hardness, corrosion resistance, and wear behavior, resulting in improved performance and extended lifespan.
Patent Information
- Application Number
- JP2022529563
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-20
- Filing Date
- 2020-11-19
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2040-11-19
AI Technical Summary
Stainless steel blast abrasives currently lack sufficient hardness and wear resistance, leading to suboptimal performance and lifespan in blasting applications.
A stainless steel blast abrasive material composed primarily of austenitic chromium manganese steel, which provides enhanced hardness, corrosion resistance, and work hardening capabilities, thereby improving wear behavior and lifespan.
The austenitic chromium manganese steel blast abrasive exhibits significantly improved hardness and lifespan compared to traditional chromium nickel steel abrasives, maintaining ductility and preventing rapid brittleness during use.
Smart Images

Figure 0007649308000001 
Figure 0007649308000002 
Figure 0007649308000003
Abstract
Description
[Technical field]
[0001] The present invention relates to stainless steel blasting abrasives and uses of stainless steel blasting abrasives. [Background technology]
[0002] Stainless steel blasting abrasives are known per se and are used in particular in the field of blasting of workpieces. In particular, stainless steel blasting abrasives are used in the blasting of workpieces made of corrosion-resistant metals or metal alloys, because otherwise the workpieces may rust due to the residues of the blasting abrasives remaining on the workpieces after blasting. Despite this problem, metal blasting abrasives are frequently used, since they usually have better wear behavior than mineral blasting abrasives. Therefore, they are particularly suitable as reusable blasting abrasives. Summary of the Invention [Problem to be solved by the invention]
[0003] There is still plenty of room for improvement in stainless steel blasting abrasives, especially in the hardness of the blasting agent and the wear behavior of the blasting agent.
[0004] Therefore, an object of the present invention is to provide an improved stainless steel blasting abrasive. [Means for solving the problem]
[0005] This problem is solved by a stainless steel blasting abrasive according to claim 1 and further by the use of a stainless steel blasting abrasive according to claim 13. Preferred embodiments of the invention are set out in the dependent claims, the description, the examples or the drawings, whereas further features described or shown in the dependent claims or the description, the examples or the drawings may, individually or in any combination, constitute the subject-matter of the invention, unless the context clearly indicates to the contrary.
[0006] The present invention proposes a stainless steel blast abrasive containing a blast abrasive component having austenitic chromium manganese steel, and the blast abrasive preferably contains austenitic chromium manganese steel in an amount of 90% by weight or more and 100% by weight or less based on the total weight of the stainless steel blast abrasive.
[0007] In the present invention, the term "blasting abrasive" means an auxiliary substance that can be used in blasting techniques for surface treatment and that can be directed at high speeds towards the workpiece or material to be blasted.
[0008] In the present invention, the term "stainless" refers to the property of being substantially inert to reactions with the environment and / or natural atmosphere. In particular, "stainless blast abrasive" refers to a blast abrasive that does not substantially react with the surrounding air and / or humidity under normal conditions.
[0009] By "blasting abrasive components" in the present invention is meant individual components of the blasting abrasive, such as, for example, individual grains, spheres or particles.
[0010] In the present invention, "chromium manganese steel" means a steel to which chromium and manganese have been added as the main alloying elements. In the present invention, steel is a material that consists mostly of iron.
[0011] In the present invention, "austenitic chromium manganese steel" means a chromium manganese steel having a predominantly austenitic structure.
[0012] By the fact that the stainless steel blast abrasive is an austenitic chromium manganese steel, it can be advantageously achieved that the blast abrasive is particularly corrosion resistant. Furthermore, in order to obtain particularly good results when using the blast abrasive, it can be achieved that the blast abrasive components have a sufficiently high hardness and at the same time a sufficient ductility. Therefore, the blast abrasive has a particularly good life. Without being bound by theory, it is assumed that the austenitic chromium manganese steel does not form a deformed martensite during cold forming, as occurs when the blast abrasive impacts the material to be blasted. This deformed martensite can rapidly embrittle known blast abrasives, thereby resulting in rapid wear.
[0013] In particular, improved hardness and improved service life of the stainless steel blast abrasive can be achieved compared to known blast abrasives made of chromium-nickel steel. Furthermore, due to the very good work-hardening tendency compared to blast abrasives made of chromium-nickel steel, it is advantageously possible to achieve an increase in hardness of the blast abrasive during use without a decrease in ductility properties.
[0014] It is contemplated that the blast abrasive may include other blast abrasive components, such as metal or mineral blast abrasive components, in addition to the blast abrasive component having an austenitic chrome manganese steel.
[0015] Preferably, the blast abrasive may be intended to include a blast abrasive component having an austenitic chromium manganese steel in the range of 95% by weight or more and 100% by weight or less, particularly preferably 98% by weight or more and 100% by weight or less, based on the total weight of the stainless steel blast abrasive.
[0016] Preferably, it may be envisaged that the blast abrasive consists of a blast abrasive component having an austenitic chromium manganese steel.
[0017] Preferably, it can be envisaged that the blast abrasive component having austenitic chromium manganese steel is made of austenitic chromium manganese steel.
[0018] By means of the above-mentioned stainless steel blasting abrasives it can be advantageously achieved that the advantageous properties of austenitic chromium manganese steels, in particular their hardness and wear behavior, can be particularly well utilized in stainless steel blasting abrasives.
[0019] Preferably, the austenitic chromium manganese steel has between 10 and 30% by weight chromium and between 6 and 30% by weight manganese, the weight percentages being based on the total weight of the austenitic chromium manganese steel.
[0020] Preferably, the austenitic chromium manganese steel has: - 0% to 0.8% by weight of carbon, - 0% to 1.2% by weight of nitrogen, - 10% to 30% by weight of chromium, - 6% to 30% by weight of manganese, - 0% to 3% by weight of molybdenum, - 0% to 3% by weight of silicon, - 0% to 2% by weight copper, - 0% to 1% by weight of cobalt, - from 0% to 1% by weight of nickel, - 0% to 1% by weight of tungsten, - 0 to 1% by weight of niobium, - 0% to 1% by weight of vanadium, - from 0% to 1% by weight of aluminium, - 0% to 1% by weight of titanium, and -The balance is iron wherein the weight percentage is based on the total weight of the austenitic chromium manganese steel, and preferably the austenitic chromium manganese steel has a total amount of carbon and nitrogen of 0.2% to 1.3% by weight.
[0021] It should be understood that the composition includes impurities caused by the melting process.
[0022] Preferably, an austenitic chromium manganese steel may be envisaged consisting of the above composition.
[0023] By virtue of the above-mentioned composition, it can be advantageously achieved that the blasting abrasive has a particularly high hardness, and that the hardness of the blasting agent increases particularly significantly and advantageously during use. Furthermore, it can be achieved that the blasting abrasive continues to have good corrosion resistance.
[0024] Preferably, the austenitic chromium manganese steel has between 15 and 19% by weight chromium and between 17 and 21% by weight manganese, the weight percentages being based on the total weight of the austenitic chromium manganese steel.
[0025] Preferably, the austenitic chromium manganese steel has: - 0.1% to 0.3% by weight of carbon, - 0.55% to 0.65% by weight of nitrogen, - 15% to 19% by weight of chromium, - 17% to 21% by weight manganese, - 0.05% to 0.15% by weight of molybdenum, - 0.7% to 1.1% by weight of silicon, - 0% to 0.5% by weight copper, - 0% to 0.5% by weight of cobalt, - from 0% to 0.1% by weight of nickel, - 0% to 0.5% by weight of titanium, - 0% to 0.5% by weight of vanadium, - 0% to 0.5% by weight of niobium and -The balance is iron wherein the weight percent ratio is based on the total weight of the austenitic chromium manganese steel, and preferably the austenitic chromium manganese steel has carbon and nitrogen in an amount of 0.7% or more and <0.9% or less by weight combined.
[0026] It should be understood that the composition includes impurities caused by the melting process.
[0027] Preferably, the austenitic chromium manganese steel has: - 0.15% to 0.25% by weight of carbon, - 0.55% to 0.60% by weight of nitrogen, - 16% to 18% by weight of chromium, - 18% to 20% by weight manganese, - 0.05% to 0.15% by weight of molybdenum, - 0.8% to 1.0% by weight of silicon, - 0% to 0.2% by weight copper, - 0% to 0.2% by weight of cobalt, - from 0% to 0.2% by weight of nickel, - 0% to 0.2% by weight of titanium, - 0% to 0.2% by weight of vanadium, - 0% to 0.2% by weight of niobium and -The balance is iron wherein the weight percent ratio is based on the total weight of the austenitic chromium manganese steel, and preferably the austenitic chromium manganese steel has a total amount of carbon and nitrogen of 0.7% to 0.85% by weight.
[0028] It should be understood that the composition includes impurities caused by the melting process.
[0029] Preferably, an austenitic chromium manganese steel may be envisaged consisting of the above composition.
[0030] Surprisingly, it has been shown that blasting abrasives having the above composition have a particularly long life.
[0031] Preferably, it may be envisaged that the austenitic chromium manganese steel has substantially no martensite structural components throughout the primary manufacturing process or does not form them during cold forming.
[0032] Preferably, it may be envisaged that the austenitic chromium manganese steel has substantially no martensite structural components throughout the primary manufacturing process and does not form them during cold forming.
[0033] It can thereby be advantageously achieved that the blast abrasive does not soften during use, and it can also be advantageously achieved in a manner that the blast abrasive does not become brittle during use with increasing hardness while maintaining the same ductility, thereby resulting in particularly advantageous wear properties.
[0034] Preferably, the austenitic chromium manganese steel has a martensitic structural component of 5% by weight or less, more preferably 1% by weight or less, particularly preferably 0.1% by weight or less throughout the primary manufacturing process and / or can be intended to be formed during cold forming, the percentages in weight being based on the total weight of the austenitic chromium manganese steel.
[0035] It may be envisaged that the blasting abrasive elements are preferably substantially concave, preferably elliptical, particularly preferably spherical.
[0036] This can advantageously be achieved so that the blasting abrasive components are deformed particularly uniformly during use, and the wear properties are further improved.
[0037] Preferably, it can be envisaged that 90% by weight or more, particularly preferably 95% by weight or more, in particular 99% by weight or more of the blasting abrasive components are substantially concave, preferably elliptical, particularly preferably spherical, based on the total amount of the blasting abrasive components.
[0038] Preferably, the blasting abrasive has a surface roughness of 3.5 g / cm3 measured according to DIN EN ISO 60:2000-01. 3 More than 5g / cm 3 Less than 4.1 g / cm 3 More than 4.6g / cm 3 It may be contemplated to have a bulk density in the following ranges:
[0039] Preferably, the blast abrasive components have a shortest and longest diameter, respectively, measured according to DIN EN ISO 11125-5:2018-12, and the blast abrasive may have a proportion of blast abrasive components whose longest diameter is more than twice as long as their shortest diameter of 15% or less, preferably 5% or less.
[0040] Preferably, the blasting abrasive component has an average equivalent diameter D measured according to DIN 66165-2:2016-08 in the range of 0.01 mm to 3 mm, preferably 0.05 mm to 2.5 mm, particularly preferably 0.09 mm to 1 mm. 50 It may be envisaged to have:
[0041] By means of the above parameters, a particularly efficient use of the blasting abrasive can be advantageously achieved.
[0042] Preferably, the blasting abrasive component has a first average equivalent diameter D50 as particles before use and a second average equivalent diameter D50 as working mixture after use, measured according to DIN 66165-2:2016-08. 50 and the second average equivalent diameter is smaller than the first average equivalent diameter, preferably at least 5% smaller, particularly preferably at least 10% smaller.
[0043] In the present invention, "fresh particles" means the blasting abrasive component before it first comes into contact with the blasting material. In the present invention, "used blasting abrasive component" means a mixture of blasting abrasive components that have been used to treat a blasting material. In particular, this means a working mixture whose weight has been completely replenished at least once by replacing the weight loss caused by use with fresh particles.
[0044] It can thereby be advantageously achieved that the blast abrasive composition changes only slightly during use up to material fatigue.
[0045] Preferably, it may be envisaged that the blasting abrasive component, as particles prior to use, has a hardness in the range of 200HV0.1 to 400HV0.1, preferably 280HV0.1 to 360HV0.1, measured according to DIN EN ISO 6507-1:2018.
[0046] As a result of this, it can be advantageously achieved that the blasting abrasive has sufficient hardness for a wide range of applications and at the same time has sufficient ductility for particularly advantageous wear properties.
[0047] It may be envisaged that the blasting abrasive component preferably has a first hardness as particles before use and a second hardness as working mixture after use, measured according to DIN EN ISO 6507-1:2018, the second hardness being greater than the first hardness, preferably at least 60% greater, more preferably at least 65% greater.
[0048] As a result of this, a further improved hardness setting for the working mixture can be achieved in an advantageous manner.
[0049] Preferably, the blasting abrasive in use has an average equivalent diameter D measured according to DIN 66165-2:2016-08 in the range of 0.3 mm to 0.01 mm. 50and can be intended to have a life of 25,000 cycles or more, preferably 28,000 cycles or more, and particularly preferably 35,000 cycles or more to 100% cumulative loss, as measured by a life test according to SAE J445-Aug2013, 5.3 "100% Replacement Method A".
[0050] As a result of this, the blast abrasive is particularly efficient and advantageously has to be replaced less frequently compared to known stainless steel blast abrasives.
[0051] Preferably, the blasting abrasive in use has an average equivalent diameter D measured according to DIN 66165-2:2016-08 in the range of 0.3 mm to 0.01 mm. 50 and may be contemplated to have an Almen strength at the saturation point of 0.20 mm or greater as measured using Almen Strip N in accordance with SAE J445-Aug2013 5.4 "Penetrated Energy Arc Height Test."
[0052] In the present invention, the saturation point is meant to be the first point on the measured curve of arc height of an Almen strip versus blast time where a doubling of the blast time causes a maximum 10% increase in arc height.
[0053] In comparison with known blasting abrasives having lower Almen strength at the saturation point, it can be advantageously achieved that the blasting abrasive has improved energy transfer when it strikes the surface to be treated, and therefore a more efficient blasting agent treatment can be advantageously achieved.
[0054] Furthermore, the present invention proposes the use of the stainless steel blasting abrasive as described above for the blasting of metal and non-metal surfaces such as surfaces, preferably workpieces, in particular stainless steel workpieces.
[0055] Further advantages and advantageous embodiments of the blasting abrasive according to the invention are shown by the examples and figures and are explained in the following description. It should be noted that the examples and figures are merely of an illustrative nature and are not intended to limit the invention in any way.
[0056] Example A Based on the total weight of austenitic chromium manganese steel 0.2% by weight of carbon, - 0.57% by weight of nitrogen, 17% by weight of chromium, 19.1% by weight manganese, 0.1% by weight of molybdenum, 0.9% by weight of silicon, 0.1% by weight of copper, 0.1% by weight of cobalt, 0.1% by weight of nickel, not more than 0.1% by weight of titanium, not more than 0.1% by weight of vanadium, - not more than 0.1% by weight of niobium and -The balance is iron The present invention provides a stainless steel blast abrasive comprising a blast abrasive component made of an austenitic chromium manganese steel having a composition comprising:
[0057] The austenitic chromium manganese steel had practically no martensitic structural components. The blasting abrasive components were spherical, with a proportion of non-spherical particles of less than 15%. The blasting agent bodies had a mean equivalent diameter D in the range of 0.01 mm to 0.3 mm, measured according to DIN 66165-2:2016-08. 50 , and had a hardness of 324±14 HV0.1 measured in accordance with DIN EN ISO 6507-1:2018.
[0058] The lifespan was examined using a shot tester (hereinafter referred to as the tester) according to SAE J445 Aug2013. For this purpose, the tester was first calibrated with a calibrated blasting abrasive. For the lifespan test, 100 g of the blasting abrasive of the present invention of Example A was loaded into the tester. For the measurement, the sample was projected at the target for 500 cycles at a shaft speed of 7800 rpm and a drum rotation speed of 25 rpm, respectively. After 500 cycles, the entire sample was sieved through a 50 μm sieve and the residue was weighed. From this, the loss was calculated and calculated relative to the number of cycles. The residue was supplemented to 100 g with unusable particles of the blasting agent of the present invention of Example A and loaded into the tester again. This procedure was repeated until the total loss reached 100 g. The number of cycles required for this quantifies the lifespan of the blasting agent. For the blasting abrasive of the present invention of Example A, the lifespan to 100% cumulative loss resulted to be more than 36,000 cycles.
[0059] The blasted abrasives obtained after the life test correspond to the working mixture. The average equivalent diameter D of the working mixture measured according to DIN 66165-2:2016-08 50 The diameter of the working mixture remained in the range of 0.3 mm to 0.01 mm, showing an overall wider distribution compared to the raw particles. The working mixture had a hardness of 575 ± 14 HV0.1 measured according to DIN EN ISO 6507-1:2018, which was more than 65% harder than the raw particles.
[0060] The Almen strength at saturation point was also examined using a shot tester according to SAE J445 Aug2013. For this purpose, the samples were projected onto Almen strips N with a thickness of 0.79 mm at a shaft speed of 7800 rpm and a drum rotation speed of 25 rpm. After 10 cycles each, the arc height of the Almen strip was measured with an Almen dial gauge and calculated against the number of cycles (Figure 4). By examining the evolution of the arc height, it was found that the saturation point was reached at 40 cycles, i.e., it was the first point at which a doubling of the blasting time (number of cycles) resulted in a maximum 10% increase in the arc height. Thus, the Almen strength at saturation point of the blasting abrasive of Example A was obtained as 0.20 mm.
[0061] (Comparative example B) Based on the total weight of chromium-nickel steel: 0.2% by weight of carbon, - 18% to 19% by weight of chromium, 8% by weight of nickel, - not more than 2% by weight of manganese, - 3% by weight or less of silicon and -The balance is iron A stainless steel blast abrasive was provided, comprising a blast abrasive component made of chromium-nickel steel having a thickness of 100 mm.
[0062] In comparison with the inventive blasting abrasive of Example A, Comparative Example B has a comparable equivalent diameter D measured according to DIN 66165-2:2016-08 in the range of 0.3 mm to 0.01 mm. 50 , and blasting abrasives having a lower hardness, i.e. a hardness of 301±11 HV0.1 measured according to DIN EN ISO 6507-1:2018.
[0063] In the comparative example, the life until the cumulative loss reached 100% was only less than 23,500 cycles. The average equivalent diameter D of the working mixture of the comparative example B measured according to DIN 66165-2:2016-08 50was almost unchanged compared to the particles before use. Moreover, the working mixture only had a hardness of 512±22 HV0.1 measured according to DIN EN ISO 6507-1:2018, which was therefore clearly lower than that of the inventive blasting abrasive of Example A. With regard to the Almen strength, the results obtained showed that the Almen strength at the saturation point after 40 cycles for the comparative example was only 0.19 mm. [Brief description of the drawings]
[0064] [Figure 1] 1 shows sieve analysis graphs of particles and working mixtures before use of the blast abrasive of the present invention of Example A and the blast abrasive made of chrome-nickel steel of Comparative Example B. [Diagram 2] 1 shows hardness analysis graphs of the particles and working mixture before use of the blast abrasive of the present invention of Example A and the blast abrasive made of chrome-nickel steel of Comparative Example B. [Diagram 3] 1 shows a graph of a life test of a blast abrasive of the present invention of Example A and a blast abrasive made of chrome-nickel steel of Comparative Example B. [Figure 4] 1 shows a graph of Almen strength for a blast abrasive of the present invention of Example A and a blast abrasive made of chrome-nickel steel of Comparative Example B. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0065] 1 shows a sieve analysis graph of the particles and working mixture of the blast abrasive of the present invention (Cr-Mn austenitic) of Example A and the blast abrasive made of chrome nickel steel (Cr-Ni austenitic) of Comparative Example B before use. Both blast abrasives have approximately the same equivalent diameter as the particles before use. The working mixture of the blast abrasive of the present invention has a greater proportion of particles with smaller equivalent diameters compared to the working mixture of Comparative Example B.
[0066] 2 shows a hardness analysis graph of the raw particles and working mixture of the blast abrasive of the present invention of Example A and the blast abrasive made of chrome-nickel steel of Comparative Example B. Both the raw particles and working mixture of the blast abrasive of the present invention of Example A are advantageously harder than the raw particles or working mixture, respectively, of the blast abrasive of Comparative Example B. Furthermore, the hardness increases between the raw particles and working mixture in the blast abrasive of the present invention, advantageously more strongly than in the comparative example.
[0067] 3 shows a graph of the life test of the blast abrasive of the present invention of Example A and the blast abrasive made of chromium-nickel steel of Comparative Example B. The calculated loss versus cycle number of the blast abrasive of the present invention is substantially flatter than that of the Comparative Example, thereby advantageously resulting in a longer life.
[0068] 4 shows a graph of the Almen strength test of the blast abrasive of the present invention of Example A and the chrome-nickel blast abrasive of Comparative Example B. Both blast abrasives have a saturation point after 40 cycles, where doubling the number of cycles results in an increase in the deflection (arc height) of the Almen strip of up to 10%. The blast abrasive of Example A has an overall higher Almen strength, from which it can be concluded that due to the comparability of the test conditions, a relatively improved energy transfer during blasting versus Comparative Example B.
Claims
1. A stainless steel blast abrasive containing a blast abrasive component having an austenitic chromium manganese steel, the blast abrasive containing 90% by weight or more and 100% by weight or less of austenitic chromium manganese steel based on the total weight of the stainless steel blast abrasive, The austenitic chromium manganese steel - 0% to 0.8% by weight of carbon, - 0% to 1.2% by weight of nitrogen, - 10% to 30% by weight of chromium, - 6% to 30% by weight of manganese, - 0% to 3% by weight of molybdenum, - 0% to 3% by weight of silicon, - 0% to 2% by weight of copper, - 0% to 1% by weight of cobalt, - 0% to 1% by weight of nickel, - tungsten, - 0 to 1% by weight of niobium, - 0% to 1% by weight of vanadium, - 0% to 1% by weight of aluminum, - 0% to 1% by weight of titanium and - The balance is iron Stainless steel blasting abrasives including.
2. 2. The stainless steel blast abrasive according to claim 1, wherein the austenitic chromium manganese steel has a total carbon and nitrogen content of 0.2% by weight or more and 1.3% by weight or less.
3. The austenitic chromium manganese steel - 0.1% to 0.3% by weight of carbon, - 0% to 0.65% by weight of nitrogen, - 15% to 19% by weight of chromium, - 17% to 21% by weight of manganese, - 0.05% to 0.15% by weight of molybdenum, - 0.7% to 1.1% by weight of silicon, - 0% to 0.5% by weight copper, - 0% to 0.5% by weight of cobalt, - 0% to 0.1% by weight of nickel, - 0% to 0.5% by weight of titanium, - 0% to 0.5% by weight of vanadium, - 0 to 0.5% by weight of niobium and - The balance is iron The stainless steel blast abrasive according to claim 1 or 2, comprising:
4. The stainless steel blasting abrasive according to any one of claims 1 to 3, wherein the austenitic chromium manganese steel has substantially no martensite structural components throughout the primary manufacturing process or is not formed during cold forming.
5. 5. The stainless steel blast abrasive according to claim 1, wherein the blast abrasive components are substantially elliptical or spherical.
6. The blasting abrasive has a surface roughness of 3.5 g / cm 3 measured according to DIN EN ISO 60:2000-01. 3 5g / cm or more 3 The stainless steel blast abrasive according to any one of claims 1 to 5, having a bulk density in the following range.
7. The stainless steel blast abrasive according to any one of claims 1 to 6, wherein the blast abrasive components have a shortest and longest diameter measured according to DIN EN ISO 11125-5:2018-12, and the blast abrasive has a ratio of blast abrasive components whose longest diameter is more than twice as long as their shortest diameter of 15% or less.
8. The blasting abrasive component has an average equivalent diameter D in the range of 0.01 mm or more and 3 mm or less, measured according to DIN 66165-2:2016-08. 50 The stainless steel blast abrasive according to any one of claims 1 to 7, comprising:
9. Use of the corrosion-resistant blasting abrasive according to any one of claims 1 to 8 for blasting metal and non-metal surfaces.
Citation Information
Patent Citations
Stainless steel ball
CN1453386A
JP1975065413A
Spherical stainless steel powder
JP1980148701A
Hard powder high in productivity and corrosion resistance with inexpensive price and projection material for shot-peening and iron-based abrasion resistant sintered alloy having hard particle dispersed
JP2016216802A